Financial inclusion and human development in the West African Economic and Monetary Union (WAEMU): the role of institutional quality - Hamidou Ouedraogo; Noël Thiombiano (Cogent Economics & Finance)
The challenge of the Sustainable Development Goals set by the United Nations is to improve the living conditions of citizens, particularly in developing countries. This is crucial for sub-Saharan African countries, as this region has one of the lowest average human development indices in the world. This study examined the role of institutional quality in the effect of financial inclusion on human development in the West African Economic and Monetary Union (WAEMU) countries from 2007 to 2022. The results using the Newey-West standard error method reveal that financial inclusion positively affects the human development index. The results also show that institutional quality amplifies the positive effect of financial inclusion on human development. These results are robust to life expectancy, education, GDP per capita, and under-five infant mortality rate. Moreover, the effects on life expectancy are greater in women than men. In terms of implications, our results suggest that improving institutional quality is a prerequisite for promoting sustainable and equitable financial inclusion. In particular, strong institutions that protect women’s rights are essential to foster inclusive human development, enabling greater participation of women in the economy.